Sequências textuais descritivas e inferências na avaliação de leitura do PISA - Mirabile, Luciana (2018)
This thesis is situated in the Reading, Writing and Portuguese Teaching research area of the Program of Postgraduate Studies in Portuguese Language at the Pontifícia Universidade Católica de São Paulo (PUC-SP) and its main subject is the descriptive textual sequences and their contribution to the inferences generation on reading. The hypothesis of this study is that descriptive textual sequences operate as textual indexes from which the reader can generate the necessary inferences in order to understand the text. Guided by this proposition, the following research question is defined: How do descriptive textual sequences contribute to the inferences generation on reading? The general objective of this research is establish a relation between the descriptive textual sequences and the inferences generation. In order to achieve this major purpose, the following specific objectives have been established: 1º) identify and describe the inferences requested in PISA questions; 2º) identify, describe and analyze the descriptive textual sequences present in the texts related to PISA questions and 3º) reflect on how the descriptive textual sequences contribute to the inference generation in reading. The theoretical contribution that underlies this research is mostly constituted by the assumptions of Text Linguistics (KOCH, 2002; 2004a; 2004b; KOCH, ELIAS, 2006), Textual Analysis of Discourses (ADAM, 2011; PASSEGGI et al., 2010; MARQUESI 2004 [1996]; 2013; 2014; 2016; 2017) and by the studies on inferences (MARCUSCHI, 1999; 2008; THURLOW & VAN DER BROEK, 1997; COLLINS, BROWN, LARKIN, 2010; GRAESSER, LOUWERSE, MCNAMARA, 2007; GRAESSER, SINGER, TRABASSO, 1994; DELL’ISOLA, 2001). The corpus consists of five PISA questions. The chosen categories of analysis are the descriptive categories in descriptive textual sequences and the inferences. The obtained results in the analysis demonstrate that descriptive textual sequences contribute to the inferences generation in reading